Evaluation of Sulfatase-Directed Quinone Methide Traps for Proteomics - Lenger, Janina (2011)
Sulfatases hydrolytically cleave sulfate esters through a unique catalytic aldehyde, which is introduced by a posttranslational oxidation. To profile active sulfatases in health and disease, activity-based proteomic tools are needed. Herein, quinone methide (QM) traps directed against sulfatases are evaluated as activity-based proteomic probes (ABPPs). Starting from a p-fluoromethylphenyl sulfate scaffold, enzymatically generated QM traps can inactivate bacterial aryl sulfatases from Pseudomonas aeruginosa and Klebsiella pneumonia and human steroid sulfatase. However, multiple enzyme-generated QMs form, diffuse, and non-specifically label purified enzyme. In complex proteomes, QM labelling is sulfatase-dependent but also non-specific. Thus, fluoromethylphenyl sulfates are poor ABPPs for sulfatases.